2016
DOI: 10.1016/j.electstud.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The political participation of disabled people in Europe: Rights, accessibility and activism

Abstract: 2 Highlights Disability is a missing socio-economic variable in political participation research. Human rights indicators of structure, process and outcomes are developed. Political equality and voting rights are denied to some groups of disabled people in national laws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 52 publications
0
21
0
1
Order By: Relevance
“…As such, the public sphere allowed the citizens to develop their agenda before presenting it in the public arena, a format that could be argued as being ideal for giving marginalized groups the necessary breathing space to develop their political agenda. Regrettably, research has shown that even accessing such basic civil rights as the right to cast votes in local, national and-in the case of EU citizens-international elections often poses a challenge for disabled people, resulting in lower voter turnout among them than non-disabled people (European Union Agency for Fundamental Rights, 2010;Priestley et al, 2016;Traustadóttir & Rice, 2017;United Nations, 2011). This draws attention to the importance of empowering disabled people to participate politically at all levels, as well as to the important role that civil society organizations have in pressuring states into actualizing human rights law (Meyers, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the public sphere allowed the citizens to develop their agenda before presenting it in the public arena, a format that could be argued as being ideal for giving marginalized groups the necessary breathing space to develop their political agenda. Regrettably, research has shown that even accessing such basic civil rights as the right to cast votes in local, national and-in the case of EU citizens-international elections often poses a challenge for disabled people, resulting in lower voter turnout among them than non-disabled people (European Union Agency for Fundamental Rights, 2010;Priestley et al, 2016;Traustadóttir & Rice, 2017;United Nations, 2011). This draws attention to the importance of empowering disabled people to participate politically at all levels, as well as to the important role that civil society organizations have in pressuring states into actualizing human rights law (Meyers, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the participation of marginalized groups, including disabled people, in policy making has been emphasized within the field of social sciences and human rights law (Charlton, 2000;Guldvik, Askheim, & Johansen, 2013;Minow, 1990;Oliver, 1990;Priestley et al, 2016;Young, 1990). Recognizing that society's structures and norms are a reflection of existing power relations, created and defined by dominant groups and which serve to maintain the status quo, Young (1990) maintains that ridding society of institutionalized domination and oppression is pivotal to achieving justice for marginalized groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, the available data illustrates that web accessibility remains persistently low. A 2004 UK study on the accessibility of public websites affirmed that less than 20 per cent of websites meets the most basic accessibility standards across the full spectrum of disabilities including hearing, motor, and sight impairment [56,57]. More recent studies tend to demonstrate that, while accessibility has increased, the majority of e-government websites among several Member States remain inaccessible to people with disabilities [58][59][60][61].…”
Section: Web Accessibility In Europementioning
confidence: 99%
“…Information about general knowledge available for the rest of society is limited, or inaccessible (Aspis 1997;Stalker 2012). Also, although progressive frameworks are becoming available (Arstein-Kerslake and Flynn 2016), people who are assessed to have 'limited mental capacity' are still systematically deprived of their legal capacity (Fundamental Rights Agency 2013;Simplican 2015) or voting rights (Priestley et al 2016;Schriner et al 1997) which makes it extremely difficult to exercise citizenship, agency or political activism. Furthermore, many self-advocacy groups work in relation to and rely on social services which makes it almost impossible for them to criticise systemic practices or more structural oppression (Aspis 1997;Buchanan and Walmsley 2006;Chappell et al 2001;Dowse 2001;Goodley 2000).…”
Section: Self-advocates In the Disabled People's Movementmentioning
confidence: 99%